Restoration of Road Pavement Depending on the Degree of Destruction of the Road - Luzhytskyi, O. F.; Kurhan, M. B.; Husak, M. A.; Ulanovskyi, V. I. (Science and Transport Progress, 2023)
Purpose. The main purpose of this work is to develop a methodology for road pavement restoration depending on the degree of road destruction. Methodology. The study is based on the recommendations of the information guide for designers and customers in the development of design solutions for the rehabilitation of public roads and a preliminary assessment of the damage caused by their destruction as a result of the armed aggression of the Russian Federation. To assess the condition of the road and determine the necessary pavement rehabilitation work, indices can be used that take into account different types of defects on the road. Comparison of different road surface options was performed using a «priority matrix». The total score for each type of pavement makes it possible to determine the most rational option. Findings. The study found that when choosing a method for organizing construction work on pavement rehabilitation, the availability of materials, technical equipment, and the timing of rehabilitation should be taken into account. The choice of pavement design and material depends on the degree of road destruction, which is determined by technical and economic indicators, taking into account the life cycle of the road. The cost of repair and maintenance over the life cycle of a pavement is a key aspect of infrastructure planning and management. Estimation of these costs helps to effectively allocate the budget, prioritize and rationally spend resources to maintain road quality. Originality. Methodological approaches to the establishment of the pavement structure by the volume and cost of materials with the adjustment of the decision made by operational indicators, taking into account the service life, resistance to traffic, wear resistance, noise, vibration and, ultimately, vehicle safety, are proposed. Practical value. The provided recommendations for road pavement rehabilitation, depending on the degree of destruction, will contribute to the adoption of effective design solutions and preliminary assessment of the damage caused by the destruction or damage to roads as a result of the armed aggression of the Russian Federation.